Canon DSLR : the ultimate photographer's guide - Grey, Christopher (Elsevier, Focal Press, 2008)
So you have a Canon DSLR? Do you know how to get the most from your sophisticated camera? Canon DSLR: The Ultimate Photographer's Guide is a thorough, in-depth and step-by-step look at how to understand the Canon digital photography system and how to optimize your digital photography workflow from pre capture to output. Chris Grey shows you how to customize your DSLR according to the genre you are working in. He showcases the work of professional photographers from the worlds of wedding photography, fine art, sports/action, portrait and nature and each photograp
Keywords: Canon digital cameras; Photography : Digital techniques; Photography